Temporal and Spatial Variations of Temperature-Humidity Index Related to Heat Stress in High-Altitude Dairy Cattle Farms - Eli Ratni; Lendrawati; Darul Islam; Kevin Ifano Rachman (Andalasian Livestock, 2025)
Heat stress is a significant concern in dairy cattle production, even in high-altitude areas typically associated with cooler climates. This study investigated the temporal and spatial variations of the Temperature-Humidity Index (THI), air temperature, and relative humidity at a high-altitude dairy farm during the rainy season in West Sumatra, Indonesia. Environmental data were collected bi-hourly from 08:00 to 16:00 at three different locations: outside the pen, inside a pen equipped with fan ventilation, and inside a pen without fan ventilation. ANOVA and Tukey post-hoc tests revealed significant differences across both time and location. The highest THI levels were recorded outside the pen during midday (12:00–14:00), with a mean of 80.18 ± 3.76, compared to 76.17 ± 1.96 in the fan-ventilated pen and 74.96 ± 1.88 in the non-ventilated pen. Notably, there were no significant differences in THI between the two indoor environments, indicating that fan ventilation had limited effectiveness. All indoor THI values reflected moderate heat stress. Additionally, Pearson correlation analysis revealed a strong negative correlation between temperature and humidity across all locations (r = -0.88 to -0.97; p < 0.05). These findings highlight the limitations of current ventilation systems and emphasize the urgent need for improved microclimate management strategies in high-altitude dairy farming.